CT Colonography: an update on current and future indications. (2nd July 2016) - Laghi, Andrea
ABSTRACT: Computed tomographic colonography (CTC) is a minimally invasive, patient-friendly, safe and robust colonic imaging modality. The technique is standardized and consolidated evidence from the literature shows that the diagnostic performances for the detection of colorectal cancer and large polyps are similar to colonoscopy (CS) and largely superior to alternative radiological exams, like barium enema. A clear understanding of the exact role of CTC will be beneficial to maximize the benefits and minimize the potential sources of frustration or disappointment for both referring clinicians and patients. Incomplete, failed, or unfeasible CS; investigation of elderly, and frail patients and assessment of diverticular disease are major indications supported by evidence-based data and agreed by the endoscopists. The use of CTC for symptomatic patients, colorectal cancer screening and colonic surveillance is still under debate and, thus, recommended only if CS is unfeasible or refused by patients.